Development of business management to expand the market and increase the competitiveness of MSMEs - Rochiyati Murniningsih; Nunik Restuti; Khusnul Ratna Sari; Novi Lili Utami; Serli Andreapuspa; Cantika Aprilia Wardani (Community Empowerment, 2022)
The community service aims to increase the application of social media usage as a digital marketing in order to expand market and increase sales. In addition, digitization is also disseminated on cash flow recording and implementation of occupational safety and health (K3) in the production scope. This activity was carried out on the “Semprong Nining” MSME located in Kramat Hamlet RT03/RW04, Gondang Village, Mungkid District, Magelang Regency. The method used is to educate partners about digital marketing and its application in social media platforms such as Instagram, Facebook, Shopee, Tokopedia, and Whatsapp Business, as well as to promote the use of the Android-based BukuKas app and hold joint discussions about strategies that must be implemented so that MSMEs can expand their market reach even further. From the activities, Partners understand and are able to use social media as a promotional tool and the BukuKas application as a digital recorder.